PENGARUH CURRENT RATIO (CR) DAN TOTAL ASET TURNOVER (TATO) TERHADAP RETURN ON ASSETS (ROA) PADA PT XL AXIATA Tbk PERIODE 2013-2023 - Marwa Arifin; Neneng Khoiriah (Journal of Research and Publication Innovation, 2024)
This study aims to determine the impact of Current Ratio (CR) and Total Asset Turnover (TATO) on Return On Asset (ROA) at PT XL Axiata Tbk for the period 2013-2023. The research employs a quantitative method. Several analyses were conducted, including: Descriptive Statistical Test, Classical Assumption Test, Simple Linear Regression Analysis Test, Multiple Linear Regression Analysis Test, Hypothesis Test, Correlation Coefficient Test (R), and Coefficient of Determination Test (R2) using SPSS version 26 software.The analysis results show that the Current Ratio (CR) variable partially does not have a significant effect on Return On Asset (ROA) at PT XL Axiata Tbk for the period 2013-2023. This is evidenced by the t-count value of 1,049 < t-table 2,306 and a significance value of 0.325 > 0.05. The Total Asset Turnover (TATO) variable partially does not have a significant effect on Return On Asset (ROA) at PT XL. Axiata Tbk for the period 2013-2023, as evidenced by the t-count value of -0,751 < t-table and a significance value of 0.474 > 0.05.With an F-count value of 0,613 < F-table 4.26 and a significance value of 0,565 > 0.05, the Current Ratio (CR) and Total Asset Turnover (TATO) variables simultaneously do not have a significant effect on Return On Asset (ROA) at PT XL Axiata Tbk for the period 2013-2023.The result of the coefficient of determination test (R2) yielded an R Square value of 0,00, indicating that the influence of the Current Ratio (CR) and Total Asset Turnover (TATO) variables on Return On Asset (ROA) is only 13,3%, while the remaining 86,7% is influenced by other variables not examined in this study.